AKTIVITAS ANTIINFLAMASI REBUSAN KULIT BATANG JAMBU METE (Anacardium occidentale L.) PADA UDEMA KAKI TIKUS TERINDUKSI KARAGENIN - Lini Veriony; Sudarsono Sudarsono; Agung Endro Nugroho (Majalah Obat Tradisional, 2011)
Hot water extract of cashew nut’s stem bark (Anacardium occcidentale L.) traditionally has been used as mouth washer to heal mouth and gum inflammation. Combination of aqueous extract of cashew nut stem bark and grape juice have anti-inflammatory activity. Cashew nut stem bark contains gallic acid and anacardic acid that had anti-inflammatory effect. The aim of this research is to observe anti-inflammatory activity of the hot water extract of Cashew nut’s stem bark compared to Indomethacin Non-Steroid Anti-inflammatory Drug. This research’s process consists of collection of the stem barks, extraction of the stem bark by hot water, qualitative analysis of gallic acid and anacardic acid, measurement total phenolic value, free radical scavenging and antiinflamatory activity assay. The hot water extract of stem bark was used to observe anti-inflammatory activity by 1.25; 2.5; 5g/kgBB and as positive control was indomethacin 10 mg/kgBB. The result of edema volume determination were counted as area under curve value and anti-inflammatory percentage and then the data were analyzed to evaluate the data difference of every group. The anti-inflammatory activity of 1.25; 2.5 and 5g/kgBB were not significantly different compared to 10 mg/kg BB indomethacin. The total phenolic concentration was gradually decreasing with the increasing concentration of the hot water extract of stem bark. The free radical scavenging DPPH activity at 1mg/mL hot water extract of stem bark was poorly than gallic acid 1mg/mL.